Challenges of Clinical Trial Design for Targeted Agents Against Pediatric Leukemias - Mussai, Francis Jay; Yap, Christina; Mitchell, Christopher; Kearns, Pamela (Frontiers in Oncology, 2015)
The past 40 years have seen significant improvements in both event-free and overall survival for children with acute lymphoblastic or acute myeloid leukemia (ALL or AML respectively). Serial national and international clinical trials have optimised the use of conventional chemotherapeutic drugs and, along with improvements in supportive care that have enabled the delivery of more intensive regimens, have been responsible for the major improvements in patient outcome seen over the past few decades,. The benefits of dose intensification, however, have likely now been maximised, and over the same period, the identification of new cytotoxic drugs has been limited. As the biology of leukemogenesis has become better understood, key molecules and intracellular pathways have been identified that offer the possibility of targeting directly the leukemia cells whilst sparing normal cells. Consequently, there is now a drive to develop novel leukemia-specific or ‘targeted’ therapies. These new classes of drugs will have mechanisms of action, toxicities and therapeutic indices quite different from conventional cytotoxic drugs previously encountered, thus rendering current clinical trial methodologies inappropriate; clinical trial methods will need to be adapted to accommodate these features of these new classes of drugs. This review will address the challenges and some of the techniques for developing clinical trials for targeted therapies.